Production for Graphic Designers. - Pipes, Alan. (Laurence King, 1992)
This introduction to pre-press and print processes emphasizes practical knowledge that will help designers to know which techniques are appropriate for a particular job, how much of the print preparation should be done in the design studio, and ways to control quality, budget and schedule.